Editors’ Introduction: Authority, Gendered Agency, and Political Negotiation in Asia - Asep Iqbal (Journal of Asian Social Science Research, 2020)
The issue of the Journal of Asian Social Science Research (JASSR), Vol. 2, No. 2, 2020, asks us to pay attention to the different faces of authority, not as abstractions, but as lived arrangements that shape political loyalty, gendered aspiration, religious commitment, and everyday conduct. It brings together five studies that are diverse in subject but closely connected in their deeper concern. They examine the political crossover of Islamic conservatism in Indonesia’s 2019 presidential election, the changing dynamics of local elections in post-Suharto Indonesia, the experiences of Muslim women academics in Indonesian state Islamic higher education, the role of women in Tablighi Jamaat’s masturah propagation in East Java, and Haji Hasan Mustapa’s Malay etiquette guidebook for Acehnese people under Dutch colonial rule. Read together, the articles show that power is never sustained by formal institutions alone. It depends on symbols, narratives, networks, gendered expectations, local brokerage, moral discipline, and historical memory.